A Call to Authentic Discipleship: Pope Benedict XVI, Kierkegaard and Entweltlichung - Emery de Gaál (Wrocławski Przegląd Teologiczny)
The article pursues the aim of demonstrating that both Pope Benedict XVI and Søren Kierkegaard call for genuine Christian discipleship. They apprehend in Christianity ever anew the danger of a bourgeois accommodation of the Christian gospel to the prevalent Zeitgeist. In the first part of this article the author presented the views of Kierkegaard, for whom threat comes from the state-established Danish Lutheran Church. The second part of the article discusses the viewpoint of Joseph Ratzinger. In his opinion, the threat may also come from a close relationship between Christianity and the state. The real danger in the 20th century was graver than that in 19th century Denmark. It comes from secularised Christology, from emphasis being put on the humanity of Jesus which ignores His divine personhood and nature. The last part of the article draws attention to the essential differences between the approaches adopted by both thinkers and the solutions proposed by them, which, however, only accentuated the greatness of these intellectuals. In his own words, Kierkegaard will always remain “a little pinch of cinnamon.” In contrast to the Danish radical Christian, by writing seminal texts from within the wisdom of the ever self-same Catholic Church, Ratzinger/Pope Benedict XVI, especially on account of his Jesus of Nazareth trilogy, inaugurates à la longue an epochal Christocentric shift. Assuredly, posterity will honour him with the title "Doctor of the Church."